Dual adaptive strategies in Candida glabrata under tunicamycin stress: petite mutations and chromosome C aneuploidy drive transient drug resistance - Dong, Yubo; Ma, Chunhua; Wang, Jing; Bai, Shuai; Wang, Chen; Xu, Yi (Frontiers in Microbiology, 2025)
BackgroundCandida glabrata is an opportunistic fungal pathogen known for its ability to rapidly develop resistance to antifungal agents. Tunicamycin (TUN), an inhibitor of N-linked glycosylation, induces Endoplasmic Reticulum (ER) stress, but the adaptive mechanisms enabling C. glabrata to survive TUN exposure remain poorly understood.ObjectiveThis study aimed to identify and characterize the genetic and phenotypic adaptations that confer TUN resistance in C. glabrata and evaluate their stability in the absence of drug pressure.MethodsWe exposed C. glabrata strain BG2 to sub-inhibitory (0.5 μg/mL) and inhibitory (1–8 μg/mL) TUN concentrations and isolated resistant mutants. Phenotypic characterization included growth assays, mitochondrial function tests (YPG medium), and fluconazole (FLC) susceptibility testing. Whole-genome sequencing assessed chromosomal alterations, and serial passaging in drug-free medium evaluated adaptation stability.ResultsUnder TUN stress, C. glabrata adopted two distinct resistance strategies: (1) mitochondrial dysfunction (petite formation), which conferred cross-resistance to FLC, and (2) aneuploidy, particularly disomy of chromosome C (ChrCx2), often accompanied by additional chromosomal gains in high-TUN conditions. However, both adaptations exhibited significant trade-offs: petite mutants retained irreversible respiratory deficiency but lost TUN and FLC resistance upon passaging, while aneuploid strains rapidly reverted to euploidy in non-selective conditions, abolishing TUN resistance.ConclusionC. glabrata survives TUN stress through unstable genetic adaptations—petite formation and aneuploidy—that are rapidly selected against in drug-free environments. These findings highlight the evolutionary constraints of antifungal resistance mechanisms and suggest that intermittent therapy may help counteract resistance development.